Protein‐Induced Color Shift of Carotenoids in β‐Crustacyanin. Issue 39 (21st July 2015) - Gamiz‐Hernandez, Ana P.; Angelova, Iva Neycheva; Send, Robert; Sundholm, Dage; Kaila, Ville R. I.
Abstract: β‐Crustacyanin (β‐CR) is a pigment protein responsible for the blue color of lobsters. We show using correlated ab initio calculations how the protein environment tunes the chromophores of β‐CR through electrostatic and steric effects. Abstract : True blue : The pigment protein β‐crustacyanin, which is responsible for the blue color of lobsters, tunes the color of its two bound astaxanthin chromophores through electrostatic polarization and steric planarization.